Should we prescribe “vasodilating” beta-blockers in Marfan syndrome to prevent aortic aneurysm and dissection? - Koraćević Goran; Sakač Dejan; Pavlović Milan; Ilić Dragana; Tomašević Miloje; Kostić Tomislav (Vojnosanitetski Pregled)
nema